Polyculture of Catfish and Kale for The Fulfillment of Independent Food in the Pandemic Era - Helmizuryani, Helmizuryani; Sari, Meika Puspita; Khotimah, Khusnul; Harmilia, Elva Dwi; Ma’ruf, Irkhamiawan; Pratami Ardina Ningrum, Puri (Universitas Muhammadiyah Palembang, 2022)
During the COVID-19 pandemic, restrictions on activities directly affected people's lives socially and economically to meet their needs of people's lives, namely by developing aquaponic technology with a fish farming system in buckets (Budikdamber). These activities maximise limited land with various crops and develop fisheries so that the results can be used to meet household food needs independently. This service was conducted for local KKN students online through a zoom meeting on September 13, 2021, with 20 participants. The implementation of aquaponics system activities considers the types of fish and vegetables recommended and the procedures for making budikdamber.